THU0440 Yersinia Enterocolitica Biotype 1A Infection can Trigger Reactive Arthritis. (23rd January 2014) - Tuompo, R.; Hannu, T.; Siitonen, A.; Leirisalo-Repo, M.
Abstract : Background: Yersinia enterocolitica (YE) is a well-known trigger of reactive arthritis (ReA) [1 ]. Studies of YE-related ReA have concentrated on the traditionally pathogenic serotypes O:3 and O:9 (biotypes 4 and 2, respectively) [2, 3 ]. Biotype 1A is generally considered non-pathogenic [4 ]. However, biotype 1A has been isolated from stools of diarrheic patients, and the potential pathogenicity of biotype 1A has been discussed in the literature [5, 6 ]. Objectives: To study the capability of YE biotype 1A to induce ReA and other reactive musculoskeletal (MS) symptoms. Methods: 406 questionnaires were sent to cases with positive stool culture of YE. Analysis of self-reported MS symptoms was supplemented with a clinical examination of subjects with recent MS symptoms. Results: Of the 295 subjects, who returned the questionnaire, 120 reported MS symptoms, of which 114 were included to the final analysis. Among these 114 patients, 77 (68%) had YE biotype 1A, 16 (14%) had YE biotype 4, and one (0.9%) had biotype 2 infection; the remaining 20 (17%) patients had different YE-like strains or had a non-biotypable strain in the stool specimens. Of the subjects, 18% (21/114) fulfilled the criteria for ReA, and a further 12% (14/114) had other reactive MS symptoms (tendinitis or enthesitis). The incidence of ReA was 6% in cases with YE biotype 1 A and 5.4% in cases with biotypes 4 or 2. Conclusions: YE biotype 1A can be a causative agent for ReA. Therefore, it should be included among pathogens searched at the diagnostic work up of the aetiology of ReA. References: Leirisalo-Repo M. Reactive arthritis. Scand J Rheumatol 2005;34:251-9. Leirisalo M, Skylv G, Kousa M, et al. Followup study on patients with Reiter's disease and reactive arthritis, with special reference to HLA-B27. Arthritis Rheum 1982;25:249-9. Schiellerup P, Krogfelt KA, Locht H. A comparison of self-reported joint symptoms following infection with different enteric pathogens: effect of HLA-B27.J Rheumatol. 2008;35:480-7. Bottone EJ. Yersinia enterocolitica: the charisma continues. Clin Microbiol Rev 1997;10:257-76. Tennant SM, Grant TH, Robins-Browne RM. Pathogenicity of Yersinia enterocolitica biotype 1A. FEMS Immunol Med Microbiol 2003;38:127-37. Bhagat N, Virdi JS. The enigma of Yersinia enterocolitica biovar 1A. Crit Rev Microbiol 2010;37:1-15. Disclosure of Interest: None Declared